A TDLAS Sensor for Simultaneous Measurement of Temperature and C2H4 Concentration Using a Differential Absorption Scheme at High Temperature - Zhang, Ting; Zhang, Gang; Liu, Xin; Gao, Guangzhen; Cai, Tingdong (Frontiers in Physics, 2020)
Ethylene (C2H4) concentration and temperature is simultaneously measured in high temperature environments using a differential absorption scheme combined with a distributed feedback (DFB) diode laser near 1. 620 μm. Based on optimal selection criteria, two wavelength pairs with absorption peaks at 6,174.58 cm−1 and 6,174.98 cm−1 are selected for the measurement. Temperatures are obtained from the ratio of the absorption cross-section of the two wavelength pairs, and C2H4 concentration is inferred from the differential absorption of one of the wavelength pairs. Measurements are performed in a high temperature cell (T = 300–900 K, P = 1 atm) to verify the accuracy of the system. The accuracies for the measurement of C2H4 concentration and temperature are 1.135 and 2.215%, respectively. Continuous time series measurements indicated that the system has a good stability, and the limit of detection achieved by Allan-Werle variance analysis is 6.6 ppm at the optimal average time of 340 s. All the measurements show the scheme is helpful for improving the practicality of laser absorption spectroscopy in combustion diagnosis.